Convergence of Comedian on Indonesian Podcast: A Study of Indonesian-Minangkabau Language Variations - Ferdiansa, Deni; Kania, Annisa Nurhijatul; Husna, Hanun Alya; Mashud, Mashud (Fakultas Ilmu Pendidikan dan Humaniora (FIPH), Universitas Muhammadiyah Semarang, 2024)
This research was motivated by the convergence phenomenon carried out by comedian Megi Irawan when he was a guest star on the PWK podcast hosted by Praz Teguh. Language convergence is an individual's strategy for adapting to the communicative behavior of the interlocutor. This research focused on the Indonesian-Minangkabau language variations used by Megi Irawan when converging on Praz Teguh. The data was obtained from two episodes of the PWK podcast featuring Megi Irawan as a guest star. This research used a descriptive qualitative approach to identify language features, convergence strategies, and social correlations. The findings showed that Megi Irawan converged using variations of the Indonesian-Minangkabau language. In the intrasystemic (internal) aspect of language, three types of Indonesian-Minangkabau language variations were found, namely phonological variations, morphological variations, and semantic variations. The convergence strategies used by Megi Irawan are code-switching, code-mixing, and interference. The findings offer significant insights into broader sociolinguistic themes. First, the research emphasizes how language variations, particularly between Indonesian and Minangkabau, reflect the identities of speakers. This aligns with sociolinguistic studies that explore how language serves as a marker of social identity and cultural belonging. Second, the findings reveal that language serves not only as a means of communication but also as a tool for building social solidarity and navigating social relationships. Third, the research contributes to ethnographic approaches in sociolinguistics by examining how language variations are tied to cultural practices and social interactions.